Pengaruh Harga Saham dan Kebijakan Hutang terhadap Deviden (Studi Kasus pada Perusahaan Pertambangan Batu Bara yang Terdfatar di Bursa Efek Indnesia Periode 2017- 2021) - Safii, Mohamad; Surahman, Hendy; Wulandari, Provita (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to determine the influence of stock prices and debt policy on dividends. Dividend policy is calculated using the dividend payout ratio. The share price is calculated by looking for calculations, namely by using the share price (closing price). Meanwhile, the debt policy uses the debt to asset (DAR) method = total debt / total assets. The method used in this research is quantitative with a purposive sampling technique. The population of this research is 31 coal mining companies listed on the Indonesia Stock Exchange and after following the sampling criteria there are 11 companies with research period of 5 (five) years. The first hypothesis is that share prices partially influence dividends. The second hypothesis is that Debt Policy partially has no effect on Dividends. The third hypothesis is that share prices and debt policies simultaneously influence dividends.